Increased sclerostin and preadipocyte factor-1 levels in prepubertal rhythmic gymnasts: associations with bone mineral density, body composition, and adipocytokine values. Issue 3 (March 2016) - Jürimäe, J.; Tillmann, V.; Cicchella, A.; Stefanelli, C.; Võsoberg, K.; Tamm, A.; Jürimäe, T.
Abstract Summary Rhythmic gymnastics as high-impact bone loading sport has positive effects on bone mineralization in prepubertal years. Sclerostin and preadipocyte factor-1 (Pref-1) are hormones that inhibit bone formation. The present study demonstrates that these hormones are higher in gymnasts, and gymnasts present higher bone mineral density (BMD) as compared to controls. Introduction Rhythmic gymnasts (RG) start their heavy trainings already in prepuberty and despite of low body fat mass (FM) and hypoleptinemia, their BMD is higher than in non-trained normal girls. The specific role of sclerostin and Pref-1, which are the inhibitors of bone formation, in bone development is not well understood. The impact of sclerostin and Pref-1 levels on BMD, body composition, and adipocytokine values was studied in prepubertal RG and untrained controls (UC). Methods Sixty-four 9–10-year-old girls were divided into RG (n = 32) and UC (n = 32) groups. Bone mineral and body composition values were measured by dual-energy X-ray absorptiometry and bone age by X-ray. Sclerostin, Pref-1, leptin, and adiponectin levels were measured from fasting blood samples. Results Sclerostin (RG 19.8 ± 6.3 pmol/l; UC 15.8 ± 5.4 pmol/l) and Pref-1 (RG 1.6 ± 1.0 ng/ml; UC 1.1 ± 0.5 ng/ml) were higher (p < 0.05) in RG compared with UC. Sclerostin was related to adiponectin (r = 0.41;p < 0.05) in UC. No relationship was found between sclerostin and Pref-1 with BMD values in prepubertal RG and age-matched UC groups. Conclusions Sclerostin and Pref-1 levels are higher in RG compared to UC girls. Specific physical activity pattern seen in prepubertal RG has a beneficial effect on bone mineralization despite increased levels of hormones that inhibit bone formation.